2012
DOI: 10.1016/j.drugalcdep.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of amphetamine-type stimulant use and associations with HIV-related risks among young women engaged in sex work in Phnom Penh, Cambodia

Abstract: Background Amphetamine-type stimulant (ATS) use has increased in Cambodia and emerged as a significant problem among female sex workers (FSWs), potentially contributing to increased risk of HIV. We examined the prevalence of ATS use and its effect on sexual risk behaviors, and sexually transmitted infections (STI) among FSWs in Phnom Penh, Cambodia. Methods A one-year prospective study among young women engaged in sex work in brothels, entertainment establishments and on a freelance basis. Socio-demographics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
81
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 61 publications
10
81
0
Order By: Relevance
“…This might have been due to the fact that females were recruited from DICs that provided services for female drug users who were involved in sex exchange drug or money. This pattern was consistent with international studies, showing instrumental use of methamphetamine among females who are involved in commercial sex work (4,26).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This might have been due to the fact that females were recruited from DICs that provided services for female drug users who were involved in sex exchange drug or money. This pattern was consistent with international studies, showing instrumental use of methamphetamine among females who are involved in commercial sex work (4,26).…”
Section: Discussionsupporting
confidence: 80%
“…During 2010 and 2011, Iran was among the countries with highest amount of methamphetamine seizure in the word (1). Methamphetamine users are highly involved with HIV related risky behaviors such as methamphetamine injection (2,3) and unsafe sexual activities (3)(4)(5). International studies also found a link between unprotected sex among female sex workers and methamphetamine use (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these limitations, our results suggest a high level of concordance between self-reported ATS use and urine toxicology results in this group of women. Results indicate high prevalence (14%) of ATS use among FSW, who are also at elevated risk of HIV and other sexually transmitted infections [3,9]. There are few, if any, community-based options for ATS users in Cambodia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has also identified drug use and, in particular, amphetamine-type stimulant (ATS) use as a serious emerging problem associated with HIV risk among FSW [3,9,10], which threatens to reverse downward trends in HIV infection rates in the region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation